Association of Co-Exposure of Antenatal Steroid and Prophylactic Indomethacin with Spontaneous Intestinal Perforation - Kandraju, Hemasree; Kanungo, Jaideep; Lee, Kyong-Soon; Daspal, Sibasis; Adie, Mohammad Amin; Dorling, Jon; Ye, Xiang Y.; Lee, Shoo K.; Shah, Prakesh S.; Beltempo, Marc; Ting, Joseph; Cieslak, Zenon; et al. (The Journal of pediatrics, 2021)
To evaluate the association of a combined exposure to antenatal steroids and prophylactic indomethacin with the outcome of spontaneous intestinal perforation (SIP) among neonates born at <26 weeks of gestation or <750 g birth weight. We conducted a retrospective study of preterm infants admitted to Canadian Neonatal Network units between 2010 and 2018. Infants were classified into 2 groups based on receipt of antenatal steroids; the latter subgrouped as recent (≤7 days before birth) or latent (>7 days before birth) exposures. The co-exposure was prophylactic indomethacin. The primary outcome was SIP. Multivariable logistic regression analysis was used to calculate aORs. Among 4720 eligible infants, 4121 (87%) received antenatal steroids and 1045 (22.1%) received prophylactic indomethacin. Among infants exposed to antenatal steroids, those who received prophylactic indomethacin had higher odds of SIP (aOR 1.61, 95% CI 1.14-2.28) compared with no prophylactic indomethacin. Subgroup analyses revealed recent antenatal steroids exposure with prophylactic indomethacin had higher odds of SIP (aOR 1.67, 95% CI 1.15-2.43), but latent antenatal steroids exposure with prophylactic indomethacin did not (aOR 1.24, 95% CI 0.48-3.21), compared with the respective groups with no prophylactic indomethacin. Among those not exposed to antenatal steroids, mortality was lower among those who received prophylactic indomethacin (aOR 0.45, 95% CI 0.28-0.73) compared with no prophylactic indomethacin. In preterm neonates of <26 weeks of gestation or birth weight <750 g, co-exposure of antenatal steroids and prophylactic indomethacin was associated with SIP, especially if antenatal steroids was received within 7 days before birth. Among those unexposed to antenatal steroids, prophylactic indomethacin was associated with lower odds of mortality.